The effectiveness of ablative and non‐surgical therapies for early hepatocellular carcinoma: Systematic review and network meta‐analysis of randomised controlled trials - Emily South; Ros Wade; Sumayya Anwer; Sahar Sharif‐Hurst; Melissa Harden; Helen Fulbright; Sofia Dias; Mark Simmonds; Ian Rowe; Patricia Thornton; Tze Min Wah; Alison Eastwood (Cancer Medicine, 2023)
Abstract Background & Aims Non‐surgical therapies are frequently used for patients with early or very early hepatocellular carcinoma (HCC). The aim of this systematic review and network meta‐analysis (NMA) was to evaluate and compare the effectiveness of ablative and non‐surgical therapies for patients with small HCC. Methods Nine databases were searched (March 2021) along with clinical trial registries. Randomised controlled trials (RCTs) of any ablative or non‐surgical therapy versus any comparator in patients with HCC ≤3 cm were eligible. Risk of bias (RoB) was assessed using the Cochrane RoB 2 tool. The effectiveness of therapies was compared using NMA. Threshold analysis was undertaken to identify which NMA results had less robust evidence. Results Thirty‐seven eligible RCTs were included (including over 3700 patients). Most were from China (n = 17) or Japan (n = 7). Sample sizes ranged from 30 to 308 patients. The majority had a high RoB or some RoB concerns. No RCTs were identified for some therapies and no RCTs reported quality of life outcomes. The results of the NMA and treatment effectiveness rankings were very uncertain. However, the evidence demonstrated that percutaneous ethanol injection was worse than radiofrequency ablation for overall survival (hazard ratio [HR]: 1.45, 95% credible interval [CrI]: 1.16–1.82), progression‐free survival (HR: 1.36, 95% CrI: 1.11–1.67), overall recurrence (relative risk [RR]: 1.19, 95% CrI: 1.02–1.39) and local recurrence (RR: 1.80, 95% CrI: 1.19–2.71). The threshold analysis suggested that robust evidence was lacking for some comparisons. Conclusions It is unclear which treatment is most effective for patients with small HCC because of limitations in the evidence base. It is also not known how these treatments would impact on quality of life. Further high quality RCTs are needed to provide robust evidence but may be difficult to undertake.